Pengaruh CEO Narcism, Corporate Social Responsibility Syariah, Profitabilitas, dan Likuiditas, Terhadap Nilai Perusahaan (Studi Empiris pada Real estate, property dan construction yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2017-2021) - Muhammad Ikhwansyah Alam; Surya Raharja (ITB AAS INDONESIA Surakarta, 2023)
This study aims to examine the influence of CEO Narcism, CSR, ROA and Liquidity on company value. The problem in this study is shown by the value of stock price growth from the property, real estate and construction sectors showing a decline in 2018 to 2020. Based on the problem, the problem in this study is: How does the CEO of Narcism, Corporate social responsibility, profitability, and liquidity affect the company's value in Real estate, property and construction listed on the Indonesia Stock Exchange for the 2017-2021 period)?. This research uses secondary data in the form of financial statements obtained through the Financial Services Authority website. This study used purposive sampling method. The population in this study is all property, real estate and construction companies whose shares have been listed on the IDX since 2017-2021. A total of 53 companies were selected as research samples during 2017-2021. The analysis method used in this study is multiple regression analysis. Based on the results of data analysis and discussion that has been put forward about the influence of CEO Narcism, CSR, ROA and Liquidity on company value, it can be concluded that ROA has proven to have a significant effect on company value, this indicates that the increase in company value is influenced by an increase in ROA, meaning ROA policy What the company does affects the value of the company. CEO Narcism, CSR and Liquidity have not proven to have a significant effect on company value.